Gender Differences in Body Image Perception among 8 th Grade Pupils (Baltic Journal of Sport and Health Sciences, 2012)
Research background and hypothesis. Previous studies have shown that dissatisfaction with the body image among girls often reflects a desire to be thinner, among boys – a desire to be bigger, taller, become more muscular and have a nice body shape. It is known that adolescents have a very precise body image which is related to their own perception. However, there is a gap in research, analyzing body image aspect, i. e. evaluation of specific body image components. Hypothesis – there is a difference in the satisfaction level with specific body image components among 8 th  grade pupils; body image assessment of 8 th  grade pupils is different in the aspect of gender. Research aim was to establish gender differences in body image perception among 8 th  grade pupils.Research methods. The research has been conducted during the months of March-April-May of 2012. A random probability sampling method was used with 8 th  grade pupils from 24 general education schools located in various cities and towns around Lithuania. The research sample was comprised of 1347 (boys n = 674, girls n = 673) 8 th  grade pupils. To perform the diagnostic analysis, the author designed a body image perception questionnaire, composed on the basis of V. Rittner (1986), A. Zaborskis et al. (1996), R. Jankauskienė (2001), A. Zaborskis, J. Makari (2001), W. D. Brettschneider, T. Kleine, G. Klimek (2003), D. M. Garner (2004), R. Russell (2004), A. Miškinytė (2011), questionnaires.Research results. Results of the present research allows concluding that respondents are more dissatisfied with their body image components which are influenced by adolescents’ phenotype. i.e. stomach, shoulders, legs, thighs, hips,  buttocks,  waist,  shin,  breast  (p